2017
DOI: 10.1002/kin.21115
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Formation via Au(III) Complex Ions Reduction with l -Ascorbic Acid

Abstract: In this paper, the kinetics and mechanism of gold nanoparticles formation during the redox reaction between [AuCl 4 ]¯complex and L-ascorbic acid under different conditions were described. It was also shown that reagent concentration, chloride ions, and pH influence kinetics of nucleation and growth. To establish rate constants of these stages, the model of Finke and Watzky was applied. From Arrhenius and Eyring dependencies, the values of activation energy (22.5 kJ mol −1 for the nucleation step and 30.3 kJ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 51 publications
3
52
0
2
Order By: Relevance
“…Again, taking into account kinetic data obtained for nucleation and growth [37], we observe the increasing value of observed rate constants for the nucleation (from 0.5 × 10 −3 to 3.6 × 10 −3 s −1 ) process, which is related to higher excess of reductant in comparison with the concentration of Au(III) ions. More reductant in reacting solution suggests that the reduction reaction of Au(III) to Au(I) and Au(I) to Au(0) is more preferable than disproponation of Au(I) to Au(0) and Au(III).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Again, taking into account kinetic data obtained for nucleation and growth [37], we observe the increasing value of observed rate constants for the nucleation (from 0.5 × 10 −3 to 3.6 × 10 −3 s −1 ) process, which is related to higher excess of reductant in comparison with the concentration of Au(III) ions. More reductant in reacting solution suggests that the reduction reaction of Au(III) to Au(I) and Au(I) to Au(0) is more preferable than disproponation of Au(I) to Au(0) and Au(III).…”
Section: Resultsmentioning
confidence: 58%
“…This fact leads to the conclusion that another mechanism, e.g., a negative charge of a dissociated form of ascorbic acid, may have influence on targeted growth of nanoparticles and thus their final shape. Taking into account kinetic data [37], we found that the process of nucleation and growth slows down with increasing amount of Au(III) ions and the reductant. The determined value of the observed rate constant for the nucleation process changes from 8.2 × 10 −3 to 3.6 × 10 −3 s −1 , and for growth this change is from 21 up to 8.9 M −1 s −1 .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The FW two‐step model, initially developed for the formation of iridium nanocluster catalysts, has been broadly used in the literature to model the kinetics of metal nanoparticle formation, including noble metal nanoparticles . Kinetic analyses of noble metal nanoparticle formation with the FW model have been reported for data collected with the more direct experimental method of ion selective electrode potentiometry (silver nanoparticles) as well as with the somewhat indirect experimental method of surface plasmon resonance (gold nanoparticles) . Other, less accessible indirect experimental methods that follow nanoparticle size have also applied the FW kinetic model to noble metal nanoparticle formation and include atomic force microscopy, X‐ray absorption fine structure and small‐angle X‐ray scattering, and synchrotron high‐energy X‐ray diffraction .…”
Section: Introductionmentioning
confidence: 99%